RISIKO HUKUM DALAM PERJANJIAN PEMBIAYAAN MURABAHAH DI PERBANKAN SYARIAH - ERIANDI ERIANDI (DIRHAM Jurnal Ekonomi Islam, 2020)
The aim of this research is to analyze the law risk in murabahah agreement in syaria banking. From its approach, this research was the normative juridical, which the research based on the literature study to get the secondary data in law areas and also to do the literature research to complete document received from the literature. The summary of this research was the law risk of murabahah agreement existed. This caused by the agreement have not fulfilled yet the syaria principle because in the agreement, the selling prices based on the total payment not form the historical prices from the products bought from the consumer which had potential risk of usury.